Pemenuhan Gizi Berdasarkan AKG Bagi Anak di Lembaga Pemasyarakatan Mengenai Hak Mendapatkan Makanan yang Layak - Setiawati, Mutiah; Mitro Subroto (UNIVERSITAS NGUDI WALUYO, 2021)
Nutritional Adequacy Rate (RDA) is the level of consumption of various essential nutrients with a value content that is used to meet the nutritional needs of an average healthy person living in a country. The AKG determination in Indonesia is based on the provisions regarding body weight for each gender, age and periodic physical activity according to the population survey. Where nutrition is a factor in child development. Children in prison have the right to obtain nutrition in accordance with the nutritional adequacy standard of 2,240 kcal / day. This has been regulated in Permenkumham No. 40 of 2017 concerning Food Administration for Prisoners, Children and Prisoners. The fulfillment of nutritional value is based on the use of food ingredients for 10 days / child. This juridical normative research focuses on literature study with three legal materials, namely primary legal materials using regulations regarding AKG standards, secondary legal materials with journals, books, research results, and documents and tertiary legal materials in the form of legal dictionaries, encyclopedias. The results showed that prisons have provided children's rights in the form of fulfillment of proper food, but it is still necessary to provide nutritional needs based on differences in children's nutritional status in order to obtain balanced nutrition according to the AKG standards that have been set so that they do not experience errors due to excess nutrition (overnutrition) and malnutrition (undernutrition). Abstrak Angka Kecukupan Gizi (AKG) merupakan tingkatan konsumsi berbagai zat gizi esensial dengan kandungan nilai yang digunakan sebagai pemenuhan kebutuhan gizi rata-rata orang sehat yang hidup disuatu negara. Penetapan AKG di Indonesia berdasarkan pada ketentuan mengenai berat badan untuk setiap gender, umur dan aktifitas fisik secara berkala sesuai dengan survei penduduk. Dimana gizi menjadi faktor dalam tumbuh kembang anak. Anak di dalam lapas berhak memperoleh gizi sesuai dengan standar kecukupan gizi sebesar 2.240 kkal/hari. Hal ini telah diatur dalam Permenkumham No 40 Tahun 2017 tentang Penyelenggaraan Makanan bagi Tahanan, Anak dan Narapidana. Pemenuhan nilai gizi didasarkan pada penggunaan bahan makanan untuk 10 hari/anak. Penelitian ini bersifat yuridis normatif yang memfokuskan pada studi kepustakaan dengan tiga bahan hukum yaitu bahan hukum primer menggunakan peraturan-peraturan mengenai standar AKG, bahan hukum sekunder dengan jurnal, buku, hasil penelitian, dan dokumen serta bahan hukum tersier berupa kamus hukum, ensiklopedia. Hasil penelitian menunjukkan bahwa lapas sudah memberikan hak anak berupa pemenuhan makanan yang layak, namun masih perlunya pemberian kebutuhan gizi berdasarkan perbedaan status gizi anak yang agar diperoleh gizi yang seimbang sesuai dengan standar AKG yang telah ditetapkan sehingga tidak mengalami kesalahan akibat kelebihan gizi (overnutrition) dan kekurangan gizi (undernutrition).